ETHICAL LEADERSHIP IN FOSTERING EMPLOYEE ENGAGEMENT AND INNOVATION THROUGH WORKPLACE WELL-BEING - Muhamad Farhan Auladi; Fatmah Bagis; Erny Rachmawati; Suyoto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
In the modern workplace, efforts to foster innovative employee behavior increasingly depend on leadership quality and individual psychological well-being. This study aims to examine the role of ethical leadership in fostering employee well-being, work engagement, and innovative work behavior in the financial services sector. A quantitative approach was employed by distributing questionnaires to respondents working in conventional and Islamic financial institutions, with a total of 192 respondents eligible for processing. Analysis was conducted using Structural Equation Modeling (SEM) to examine the interrelationships between variables and identify the mediating role of work engagement. The results of the study show that ethical leadership has a positive effect on employee well-being and increases work engagement. Furthermore, work engagement has been shown to act as a psychological mechanism that strengthens the influence of ethical leadership on innovative work behavior. Work well-being also supports increased innovation through more stable and positive psychological drives. This study emphasizes the importance of ethical leadership practices as a foundation for organizations in fostering a healthy work environment and encouraging continuous innovation. These findings provide opportunities for financial institutions to formulate human resource development strategies that are more oriented towards ethics and well-being.